2018
DOI: 10.1126/science.aao0666
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular dendritic cells elicit anaphylaxis by relaying allergens to mast cells via microvesicles

Abstract: Anaphylactic reactions are triggered when allergens enter the blood circulation and activate IgE-sensitized mast cells (MCs) causing systemic discharge of prestored proinflammatory mediators. Since MCs are extravascular, how they perceive circulating allergens remains a conundrum. Here, we describe the existence of a CD301b+ perivascular dendritic cell (DC) subset that continuously samples blood and relays antigens to neighboring MCs, which vigorously degranulate and trigger anaphylaxis. DC antigen-transfer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…To confirm that significant MC activation occurred following platelet activation, we examined collagen and epinephrine-treated mice for signs of shock, a classical manifestation of systemic MC activation. It is known that when mice are subjected to immunoglobulin E (IgE)-mediated MC activation, they experience anaphylaxis, which is indicated by a sharp drop in core body temperature (13). We observed that collagen and epinephrine-treated mice experienced a sharp drop in core body temperature, which was attributable to MC activation based on the high levels of chymase-a major prestored MC mediator (10)-detected in the plasma of these mice ( Fig.…”
Section: Platelets Aggregate In Microvasculature In Close Proximity Tmentioning
confidence: 84%
See 2 more Smart Citations
“…To confirm that significant MC activation occurred following platelet activation, we examined collagen and epinephrine-treated mice for signs of shock, a classical manifestation of systemic MC activation. It is known that when mice are subjected to immunoglobulin E (IgE)-mediated MC activation, they experience anaphylaxis, which is indicated by a sharp drop in core body temperature (13). We observed that collagen and epinephrine-treated mice experienced a sharp drop in core body temperature, which was attributable to MC activation based on the high levels of chymase-a major prestored MC mediator (10)-detected in the plasma of these mice ( Fig.…”
Section: Platelets Aggregate In Microvasculature In Close Proximity Tmentioning
confidence: 84%
“…Because the genetic elements of Mcpt5 drive tdTomato expression in MCs, red fluorescence is mostly cytoplasmic and does not readily denote degranulation. Therefore, to evaluate the actual degranulation of MCs, we stained MC granules by using avidin, which is routinely used for MC granule staining (8,13), and found that several of these MCs showed signs of degranulation ( Fig. 1F).…”
Section: Platelets Aggregate In Microvasculature In Close Proximity Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In allergic patients, small amounts of allergen activate mast cells and trigger an immune cascade that can result in anaphylactic shock. In a recent issue of Science, Choi et al (2018) show that dendritic cells sample the lumen of blood vessels and use microvesicles to trigger mast cell degranulation and anaphylaxis.…”
mentioning
confidence: 99%
“…Therefore, research that addresses the current gaps in understanding of how minor amounts of allergen can trigger IgE-mediated immune responses that result in anaphylactic shock has become imperative to develop effective novel treatment strategies for allergic patients. In a recent article in Science, Choi et al describe a novel form of innate immune communication that provides an explanation of how minor amounts of antigen in circulation efficiently induces massive mast cell degranulation (Choi et al, 2018).…”
mentioning
confidence: 99%